Digital Enablement Under Care Constraints: Determinants of Women-Led Enterprises in Indonesia - Axellina Muara Setyanti; Silvi Asna Prestianawati; Andi Tri Setiawan; Muhammad Fawwaz; Muhammad Fansurullah Harsa (UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose—This study examines the determinants of digital enablement among women-led enterprises in Indonesia, focusing on the roles of care responsibilities, household structure, and human capital. It seeks to understand how domestic constraints and socio-economic characteristics influence women entrepreneurs’ participation in digitally mediated economic activities. Design/methodology/approach—The analysis uses nationally representative cross-sectional microdata from the 2024 National Socioeconomic Survey (SUSENAS). Digital enterprise participation is defined as the use of digital tools to sell goods or services. A binary logistic regression model is employed to estimate the determinants of digital participation, complemented by rural–urban subgroup analysis to capture spatial heterogeneity. Findings—Childcare responsibilities are positively associated with digital participation, particularly in rural areas, suggesting that digital enterprise functions as a flexible response to care constraints. In contrast, a larger household size reduces the likelihood of digital engagement, reflecting cumulative domestic pressures. Education significantly increases digital participation, with stronger effects in urban contexts. Handphone ownership emerges as the strongest predictor across all models, highlighting the importance of digital access. Household-head status shows differing effects between rural and urban areas, indicating that intra-household authority interacts with local economic environments. Research implication/limitation—This study enriches the literature on digital entrepreneurship and gendered labor markets by integrating household dynamics, care responsibilities, and spatial inequality into the analysis of digital participation. Originality/value—The cross-sectional nature of SUSENAS limits causal inference. Nonetheless, the findings highlight the need for gender-responsive and place-sensitive digital inclusion policies to support women entrepreneurs.